2003
DOI: 10.1046/j.1471-4159.2003.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte injury in multiple sclerosis: a role for p53

Abstract: Multiple sclerosis (MS) is a neurological disorder characterized by myelin destruction and a variable degree of oligodendrocyte death. We have previously shown that overexpression of the transcription factor p53 can induce oligodendrocyte apoptosis. We investigated the mechanism of p53-induced apoptosis using primary cultures of central nervous system-derived adult human oligodendrocytes. Adenovirus-mediated p53 overexpression resulted in up-regulation of the death receptors Fas, DR4 and DR5 with subsequent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 55 publications
3
67
0
Order By: Relevance
“…An additional difference between these two neuropathological findings is the presence of remyelination attempts that are frequently detected in the immunemediated forms and are less prominent in cases with extensive oligodendrogliopathy (Lucchinetti et al, 2000). Very little is known regarding the causes of oligodendroglial death in MS patients; however, increased levels of the pro-apoptotic transcription factor p53 and of its downstream genes have been detected in cases characterized by oligodendrogliopathy, microglial infiltration, and relative lack of remyelination (Kuhlmann et al, 2002;Aboul-Enein et al, 2003;Wosik et al, 2003;Stadelmann et al, 2005). Studies in cultured human oligodendrocytes further identified p53 as a critical pro-apoptotic effector (Ladiwala et al, 1999;Wosik et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional difference between these two neuropathological findings is the presence of remyelination attempts that are frequently detected in the immunemediated forms and are less prominent in cases with extensive oligodendrogliopathy (Lucchinetti et al, 2000). Very little is known regarding the causes of oligodendroglial death in MS patients; however, increased levels of the pro-apoptotic transcription factor p53 and of its downstream genes have been detected in cases characterized by oligodendrogliopathy, microglial infiltration, and relative lack of remyelination (Kuhlmann et al, 2002;Aboul-Enein et al, 2003;Wosik et al, 2003;Stadelmann et al, 2005). Studies in cultured human oligodendrocytes further identified p53 as a critical pro-apoptotic effector (Ladiwala et al, 1999;Wosik et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known regarding the causes of oligodendroglial death in MS patients; however, increased levels of the pro-apoptotic transcription factor p53 and of its downstream genes have been detected in cases characterized by oligodendrogliopathy, microglial infiltration, and relative lack of remyelination (Kuhlmann et al, 2002;Aboul-Enein et al, 2003;Wosik et al, 2003;Stadelmann et al, 2005). Studies in cultured human oligodendrocytes further identified p53 as a critical pro-apoptotic effector (Ladiwala et al, 1999;Wosik et al, 2003). We thereby hypothesized that this transcription factor could play a very important role in models of primary demyelination consequent to oligodendrocyte dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, recent observations suggest that the tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) could play a role in the pathogenesis of MS, as its increased activity is associated with detrimental effects on oligodendrocytes. 7,8 TRAIL is a recently characterized member of the TNF superfamily that binds to five specific membrane receptors. 9,10 Among these, receptors DR4 and DR5 are type I membrane proteins and belong to the TNF/NGF receptors superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, p53 knock out or pharmacological inhibition of p53 decreased the extent of demyelination. 40,41 SLFN1 has been shown to cause growth inhibition and a G1 cell cycle arrest in murine fibroblasts, while other reports suggested that SLFN1 was associated with immune response, but without anti-proliferative activities. 42 The only one down-regulated gene in CPZ-exposed mice was Mre11a.…”
Section: Cuprizone Induced Cell Cycle Activationmentioning
confidence: 98%